Gender balance and geographical diversity in editorial boards of Geochimica et Cosmochimica Acta and Chemical Geology - Olivier Pourret; Pallavi Anand; Pieter Bots; Elizabeth Cottrell; Anthony Dosseto; Ashley Gunter; David W. Hedding; Daniel Enrique Ibarra; Dasapta Erwin Irawan; Karen Johannesson; Jabrane Labidi; Susan Little; et al. (European Science Editing)
Background: Members of editorial boards of academic journals are often considered gatekeepers of knowledge and role models for the academic community. Editorial boards should be sufficiently diverse in the background of their members to facilitate publishing manuscripts representing a wide range of research paradigms, methods, and cultural perspectives.Objectives: To critically evaluate changes in the representation of binary gender and geographic diversity over time on the editorial boards of Chemical Geology and Geochimica et Cosmochimica Acta, flagship geochemistry journals, respectively, from the European Association of Geochemistry and the Geochemical Society – Meteoritical Society partnership.Methods: The composition of editorial boards was ascertained as given in the first issue of each year, over 1965–2021 for Chemical Geology and 1950–2021 for Geochimica et Cosmochimica Acta, and members of the editorial boards were coded for their country of affiliation (the country of origin may have been different) and for their binary gender.Results: Gender parity, limited to men and women, and the number of countries of affiliation increased steadily between the late 1980s and 2021. However, the geographic distribution remained dominated by affiliations from North America and Western Europe. The editor-in-chief or board of editors had a significant impact on the diversity of the editorial boards, and both geographic and gender diversity may evolve with nearly every newly appointed editor. However, the persistently substantial under-representation on editorial boards of affiliations outside North America and Europe is of concern and needs to be the focus of active recruitment and ongoing monitoring. This approach will ensure that traditionally low geographic diversity is increased and maintained in the future.Conclusion: Improving diversity and inclusion of editorial boards of academic journals and strengthening journal and disciplinary reputations are mutually reinforcing. Instituting a rotating editorship with emphasis on embedding broader geographic networks and more equitable international recruitment could ensure sustained and wider geographic representation and gender balance of editorial boards and promote originality and quality of published research, representing our global communities.